Answer:
x= -1 and y= -1
Explanation:
Power through with me as I explain this, its a bit long of an explanation.
To solve the following system of equations, we need to write 5x-4y=-1 in slope-intercept form.
![5x -4y= -1](https://img.qammunity.org/2023/formulas/mathematics/high-school/g3dr5wuezs57uzu72f8n45jm37taznx0ol.png)
Subtract 5x from both sides.
![5x-5x -4y= -1 -5x](https://img.qammunity.org/2023/formulas/mathematics/high-school/mny18716ekxk81fce4ybb898lfxzfb4oj1.png)
![-4y= -1-5x](https://img.qammunity.org/2023/formulas/mathematics/high-school/svh6k0dj132btba5a0im144kpaagn2el43.png)
Divide each term by -4.
![(-4y)/(-4) = (-1)/(-4) + (-5x)/(-4)](https://img.qammunity.org/2023/formulas/mathematics/high-school/mhhur0p3h8h5f8chsoef6bjx57hxo5dmm6.png)
Remember that dividing two negative values results in a positive value.
![y= (1)/(4) + (5x)/(4)](https://img.qammunity.org/2023/formulas/mathematics/high-school/hv2ea75z16ovfzuybxdx86185d3b0xaw5d.png)
Reorder the terms. (Reordering terms makes the work tidier, it does not change the result)
![y= (5)/(4) x+ (1)/(4)](https://img.qammunity.org/2023/formulas/mathematics/high-school/e6js2adf2lx39tfhz232gifyezfrg9rjo8.png)
Now that we have the slope-intercept form, we can solve by subsitution with the two equations to find the solution.
Substitute
for y in
.
![(5)/(4) x+(1)/(4) = 6x + 5](https://img.qammunity.org/2023/formulas/mathematics/high-school/ko0g58t8gfe9tla7m23ijak3o883scz633.png)
Subtract 1/4 from each side.
![(5)/(4)x+(1)/(4)-(1)/(4)=6x+5-(1)/(4)](https://img.qammunity.org/2023/formulas/mathematics/high-school/gstynfyubpfecyjy5w8z4zhvwqu0qhyhzy.png)
Simplify the left side.
![(5)/(4)x=6x+5 -(1)/(4)](https://img.qammunity.org/2023/formulas/mathematics/high-school/3u6lmsiwnwdy0lkrp2jejbdyl1jl5r3jsm.png)
Simplify the right side.
![(5)/(4)x=6x+(19)/(4)](https://img.qammunity.org/2023/formulas/mathematics/high-school/lm31gmalnslfjz9lgh7lqjw0lxtf56vc09.png)
Subtract 6x from both sides.
![(5)/(4)x-6x=6x+(19)/(4)-6x](https://img.qammunity.org/2023/formulas/mathematics/high-school/sec7rtucoiaf16c3jvrt7km9koufbidy7x.png)
Simplify.
![(5)/(4)x-6x=(19)/(4)](https://img.qammunity.org/2023/formulas/mathematics/high-school/1e1u4o1mbycmnqmgykgdoib93z0x5zcq7k.png)
Simplify the left side of the equation by factoring out x.
![x((5)/(4) -6)= (19)/(4)](https://img.qammunity.org/2023/formulas/mathematics/high-school/mt29c3dimbrx9uh7b2f18mujvvme051lpr.png)
![x(-(19)/(4) )=(19)/(4)](https://img.qammunity.org/2023/formulas/mathematics/high-school/pmuwczay3r2lahystatufpezyyqhktzlnr.png)
![-(19)/(4) x=(19)/(4)](https://img.qammunity.org/2023/formulas/mathematics/high-school/xqcbwlu8iixv5qe61nb86a68ffj5r7rvfv.png)
Multiply each side by 4.
![4\left(-(19)/(4)x\right)=(19*4)/(4)](https://img.qammunity.org/2023/formulas/mathematics/high-school/og3qdwygq85w3mze5ql99hsnbwv7icf0vc.png)
![-19x=19](https://img.qammunity.org/2023/formulas/mathematics/high-school/i8vahfoxv79303s26l4u5y13s9qxcfn1za.png)
Divide both side by 19.
![(-19x)/(-19)=(19)/(-19)](https://img.qammunity.org/2023/formulas/mathematics/high-school/hn3miyudr3ocbufmn7jeh4hsqlzmwfdodw.png)
![x= -1](https://img.qammunity.org/2023/formulas/mathematics/high-school/gcmp46wifg1w2vr3127vm9cleotlkcktc2.png)
Now that we know the value of x, we need to find y.
Insert the value of x in the equation y= 6x+5
![y= 6(-1) +5](https://img.qammunity.org/2023/formulas/mathematics/high-school/46b5fh2ccyqc9xb8cvdurf24ojmq5w5aur.png)
![y=-6+5](https://img.qammunity.org/2023/formulas/mathematics/high-school/nqjeck2ubesu10w4gtnvoz2blo1f2tahyb.png)
![y=-1](https://img.qammunity.org/2023/formulas/mathematics/high-school/vwgcxbnu6slshz866yc5mzof7h9jqvl6lx.png)
Thus, x= -1 and y= -1 OR (-1,-1)